Emerging Applications of Medical Physics in Environmental Health Monitoring: A Novel Approach to Radiation and Pollution Assessment - Hattan, Hussein Ali Abdul Amir; Jabbar, Karar Habib Nemeh; Mehaisen, Aalaa Fadhel Fenjan; Dahl, Noor Salih Ibrahim; Khilaf, Rasha Hassan Ajeel (American Journal of Botany and Bioengineering, 2025)
Medical physics has emerged as a multidisciplinary field bridging physics, biology, and environmental science, yet its full potential in environmental health monitoring remains underexplored. This study addresses a key knowledge gap by investigating how medical physics tools—traditionally confined to clinical diagnostics and therapy—can be adapted for real-time assessment of radiation and pollution risks in diverse environments. Using an interdisciplinary approach, we employed low-cost Geiger-Muller–based dosimetry systems and advanced spectroscopic sensors to evaluate ionizing radiation levels, water contaminants, and air quality in healthcare and urban settings. The findings demonstrate that integrating portable, open-source detectors with smartphone applications enhances accessibility, data storage, and immediate hazard response. Results showed significant improvements in monitoring accuracy, coverage, and public health readiness, especially in resource-limited environments. These insights underscore the transformative implications of medical physics for proactive environmental health surveillance and pave the way for its integration into sustainable public health policies.